Gecko Adhesion on Wet and Dry Patterned Substrates. - Alyssa Y Stark; Amanda M Palecek; Clayton W Argenbright; Craig Bernard; Anthony B Brennan; Peter H Niewiarowski; Ali Dhinojwala (PLoS ONE, 2015)
Perhaps one of the most astounding characteristics of the gecko adhesive system is its versatility. Geckos can locomote across complex substrates in a variety of conditions with apparent ease. In contrast, many of our synthetic pressure sensitive adhesives fail on substrates that are dirty, wet or rough. Although many studies have investigated the effect of environmental challenges on performance, the interaction of multiple, potentially compromising variables is studied less often. Here we focus on substrate structure and surface water, both of which are highly relevant to the biological system and to synthetic design. To do this we utilized a highly controlled, patterned substrate (Sharklet®, by Sharklet® Technologies Inc.). This allowed us to test independently and jointly the effects of reduced surface area substrates, with a defined pattern, on adhesion in both air and water. Our results show that adhesion is not significantly impaired in air, whereas surface area and pattern significantly affect adhesion in water. These findings highlight the need to study multiple parameters that are relevant to the gecko adhesive system to further improve our understanding of the biological system and to design better, more versatile synthetics.